COST EFFICIENCY OF BANKING SECTOR OF INDONESIA: EVIDENCE USING STOCHASTIC FRONTIER ANALYSIS - Romauli Nainggolan (International Journal of Accounting, Finance and Business, 2020)
Malaysia shows the highest sustainability disclosure rate (64.5%) among the five ASEAN countries followed by Singapore (61.7%), Thailand (60%), the Philippines (56.3%) and Indonesia (53.6%). Based on the KPMG’s Survey of Corporate Reporting 2017, 97% of top 100 Malaysian PLCs have published their sustainability performance compared to the world average of 72%. This reveals that Malaysian PLCs are concerned on the importance of sustainability reporting and sustainability performance. Therefore, this study aims to assess the sustainability performance in relation to financial performance. This study also examines factors influencing the sustainability performance. A sample of 39 PLCs from ten industries over 2010 to 2018 are chosen in this study. The sustainability performance is measured by ESG score, which is obtained from Thomson Reuters. This study has four independent variables, namely firm size, leverage, profitability and economic performance. Pearson correlation and multiple regression tests are conducted to meet the objectives of study. The findings show that profitability and size of company have positive and significant impact towards the sustainability performance. Also, the sustainability reporting has an influence on the company financial performance. Essentially, this study bridges the knowledge gap of establishing a relationship between sustainability with firm performance considering three pillars of sustainability, namely environmental, social and governance.